Machine Knowledge and Human Cognition - Fashen Li; Lian Li; Jianping Yin; Liang Huang; Qingguo Zhou; Ning An; Yong Zhang; Li Liu; Jialin Zhang; Kun Kuang; Lei Yang; Zhixi Wu; et al. (Big Data Mining and Analytics)
Intelligent machines are knowledge systems with unique knowledge structure and function. In this paper, we discuss issues including the characteristics and forms of machine knowledge, the relationship between knowledge and human cognition, and the approach to acquire machine knowledge. These issues are of great significance to the development of artificial intelligence.